Diving behaviour of lactating bearded seals ( Erignathus barbatus) in the Svalbard area - Krafft, Bjørn A; Lydersen, Christian; Kovacs, Kit M; Gjertz, Ian; Haug, Tore (Canadian Journal of Zoology, 2000)
This study documents activity patterns and diving behaviour of four bearded seal (Erignathus barbatus) mothers during the lactation period. The females spent 8 ± 3% (mean ± SD) of their time hauled out on the ice and 92 ± 3% in the water. Approximately half of their time was spent diving. During the study 15 077 dives were recorded. The duration of dives was 2.0 ± 2.3 min and diving depth was 17.2 ± 22.5 m (maximum 18.7 min and 288 m, respectively). Haulout periods occurred 3 ± 2 times per day (duration = 44.0 ± 98.1 min). The overall distance swum per day was 48.1 ± 23.2 km. Three dive types were differentiated using a combination of hierarchical and k-means clustering, one V-shaped grouping and two U-shaped groupings. The most common dive type was U 1 these dives were the deepest and longest type (depth = 28 ± 32 m, duration = 185 ± 146 s), and bottom time occupied a significant fraction of the total dive time (120 ± 120 s). These dives are likely foraging dives. Lactation is energetically demanding for bearded seals, and females do forage while they have dependent pups.